L’autoévaluation du stress au travail : un indicateur de santé trompeur - Michel Vézina; Renée Bourbonnais; Alain Marchand; Robert Arcand (Perspectives Interdisciplinaires sur le Travail et la Santé)
The purpose of this study is to document the relationships between some psychosocial constraints in the workplace and some mental health problems based on data for Québec from Cycle 1.2 of the Canadian Community Health Survey. From 2002 to 2005, results indicate a significant increase in weak social support from 45% to 49%, while for the same period, the number of persons indicating being stressed at work decreased significantly, dropping from 42% to 38%. However, while less autonomy in the workplace is associated with less stress at work, this dimension is also recognized as pathogenic for mental health. Therefore, self-assessment of stress in the workplace appears to be a misleading health indicator, since it fails to assess dimensions recognized as pathogenic for mental health.